The status of broadband in western Greece: a study on the supply and the demand of Broadband Services for e-Government promotion - Christos Bouras; J Papagiannopoulos; S Katsikas; S Gritzalis (International Journal of Electronic Governance (IJEG), Interscience Publishers, Vol. 1, No. 3, 2008)
Fast and reliable access technology is necessary for developing efficient and effective e-Government services. The existence of a direct relationship between the presence of a broadband network and the availability of e-Government services has frequently been debated in the literature. This paper presents the results of a study conducted by the RACTI (Research Academic Computer Technology Institute), which investigates the current status of broadband with regards to the demand for and the supply of broadband services and infrastructures that will support these services, in the Western Greece Region. Broadband promotes open effective governance and improved services to citizens while creating a new economy based on knowledge. Broadband development has a significant impact on e-Government support and diffusion.